ANALISA HUKUM ATAS KEKERASAN TERHADAP WARGA SIPIL AKIBAT PEPERANGAN YANG TERJADI DI ALEPPO SURIAH BERDASARKAN KETENTUAN KONVENSI JENEWA 1949 - Syarifah Tiffany Nargis; Chairul Bariah; Makdin Munthe (Journal of USU International Law, 2017)
THE LEGAL ANALYSIS OF VIOLENCE TO CIVILIANS DUE TO WAR IN ALEPPO SYRIA BASED ON PROVISIONS IN GENEVA CONVENTION 1949ABSTRACTProtection values for civilians are stipulated in Geneva Convention 1949. It is regulated that anyone, even when an enemy is captured, still he must be treated well by respecting his dignity and prestige as a human being. There is a tendency to observe that the provisions of Geneva Convention 1949 do not only regulate the obligations of member countries but also civilians’ individual human rights as the protected party. The non-international armed war in Syria is a resistance to Geneva Convention 1949. The research problems are: How the position of Geneva Convention IV 1949 is in International Humanitarian Law, How Geneva Convention plays its role in protecting civilians in the time of war, and how the legal protection for the civilians is from the violence in Aleppo due to the war in Aleppo Syria according to Geneva Convention 1949. This is a research with normative juridical method which employs statutory approach. It is also a doctrinaire research that refers to legal norms; thus, it puts emphasis on secondary legal materials, either regulations or legal theories which focus on collecting all relevant laws in the books, studying the laws related to legal provisions and the implication of its implementation in Indonesia or the law pronounced through research process. The results show that the position of Geneva Convention IV 1949 in International Humanitarian Law is a part of Humanitarian Law to protect military personnel who no longer take part in war and people who are not active anymore in a war i.e. civilians. The role of Geneva Convention to protect the civilians in the time of war is a part of humanitarian law which regulates legal protection for civilians is that it must not be carried out discriminatively. In all circumstances, civilians are entitled to respect for their persons, their honor, their family rights, their religious convictions and practices. The legal protection for the civilians from violence in Aleppo due to the was in Aleppo Syria according to the Geneva Convention 1949 is grounded on Article 27 of Geneva Convention IV saying that Protected persons are entitled, in all circumstances, to respect for their persons, their honor, their family rights, their religious convictions and practices, and their manners and customs. Keywords: Violence, Aleppo, Syria, Civilian, Geneva Convention IV